"Visita del ministro de Instruccion y Sanidad. En la guarderia infantil". Place of persons indicated on the back. Series of 2 photos. Copied from CNT collection
"Visita del ministro de Instruccion y Sanidad. En la guarderia infantil". Place of persons indicated on the back. Series of 2 photos. Copied from CNT collection.